2001
DOI: 10.1038/ng765
|View full text |Cite
|
Sign up to set email alerts
|

MLL translocations specify a distinct gene expression profile that distinguishes a unique leukemia

Abstract: Acute lymphoblastic leukemias carrying a chromosomal translocation involving the mixed-lineage leukemia gene (MLL, ALL1, HRX) have a particularly poor prognosis. Here we show that they have a characteristic, highly distinct gene expression profile that is consistent with an early hematopoietic progenitor expressing select multilineage markers and individual HOX genes. Clustering algorithms reveal that lymphoblastic leukemias with MLL translocations can clearly be separated from conventional acute lymphoblastic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
1,279
3
21

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,709 publications
(1,355 citation statements)
references
References 42 publications
52
1,279
3
21
Order By: Relevance
“…The occurrence of lineage switches with high frequency in MLL-positive AL compared to other leukemias is thus another distinctive trait that also suggests that MLL-AL originates from an immature precursor. This fact, together with the different biological characteristics, clinical features, response to treatment and outcome, support the proposal that this AL subtype should be considered as a different entity [27]. Moreover, blasts from infant MLL-positive forms of ALL typically express a unique marker profile: CD10-negative with co-expression of myeloid antigens (CDw65 and CD15), also suggesting that they derive from a precursor cell with a shared Bcp lympho-myeloid differentiation potential [10].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The occurrence of lineage switches with high frequency in MLL-positive AL compared to other leukemias is thus another distinctive trait that also suggests that MLL-AL originates from an immature precursor. This fact, together with the different biological characteristics, clinical features, response to treatment and outcome, support the proposal that this AL subtype should be considered as a different entity [27]. Moreover, blasts from infant MLL-positive forms of ALL typically express a unique marker profile: CD10-negative with co-expression of myeloid antigens (CDw65 and CD15), also suggesting that they derive from a precursor cell with a shared Bcp lympho-myeloid differentiation potential [10].…”
Section: Discussionsupporting
confidence: 68%
“…Several hypotheses have been proposed for explaining lineage conversions. Gene profiling studies on samples from cases of MLL positive AL revealed patterns half way between AML and ALL, also consistent with early hematopoietic progenitors [27]. In addition, as stated above, the presence of early bipotential B-macrophage progenitors in normal bone marrow has been demonstrated, raising the possibility that the lineage switching event would be consequence of the leukemogenic mutation targeting this early bi-potential progenitor cell [7,8,47].…”
Section: Discussionmentioning
confidence: 53%
“…61 In gene expression profiling (GEP) studies, MLL-rearranged cases clustered together as one group in AML as well as in ALL. 13,[62][63][64] However, our laboratory showed that within MLL-rearranged infant ALL each type of MLL translocation is associated with a translocation-specific gene expression signature. 65 We identified a specific gene expression signature for the total group of MLL-rearranged AML cases, 12 but were also able to identify a specific signature for t(9;11)(p22;q23).…”
Section: Epidemiology Of Mll Aberrations In Pediatric Amlmentioning
confidence: 89%
“…Gene expression analyses revealed HOX gene dysregulation in all types of MLL fusion-associated T-and B-cell acute lymphoblastic leukemias (Rozovskaia et al, 2001;Armstrong et al, 2002;Yeoh et al, 2002;Ferrando et al, 2003), implicating HOX genes as integral factors in MLL fusion-associated leukemias. Furthermore, leukemias associated with MLL rearrangements show upregulation of HOXA9 and MEIS1 (Yeoh et al, 2002;Kohlmann et al, 2003;Tsutsumi et al, 2003;Fine et al, 2004), which, as discussed below, may be a common pathway that unifies diverse initiating events in many myeloid leukemias.…”
Section: Mll Fusion Genesmentioning
confidence: 99%